Report of albinism in Podiceps major, Pelecanus thagus y Cinclodes fuscus and a revision of wild albino birds from Peru - Torres, Miriam (2008)
We report observations of albino individuals in three species of Peruvian birds, Great Grebe (Podiceps major), Peruvian Pelican (Pelecanus thagus) and Bar-winged Cinclodes (Cinclodes fuscus). These were all three mostly white partial albinos, apparently adult birds that showed normal behavior among normal conspecific individuals. Survival after several months was confirmed for the Peruvian Pelican and the Bar-winged Cinclodes. Since published information on albinism in Peruvian birds is very scarce, a revision was made and records for nine other species were compiled and are also presented.